Identification of a novel norketamine precursor from seized powders: 2-(2-chlorophenyl)-2-nitrocyclohexanone. (April 2022) - Yen, Yao-Te; Tseng, Shih-Hao; Huang, Deng-Ying; Tsai, Yi-Shiuan; Lee, Li-Wen; Chen, Pei-Lin; Liu, Yuh-Lin; Chyueh, San-Chong
Highlights: ● Seized powder was identified as 2-(2-chlorophenyl)- 2-nitrocyclohexanone. ● 2-(2-chlorophenyl)- 2-nitrocyclohexanone is a precursor in norketamine synthesis. ● Norketamine has similar pharmacological effects to ketamine, that is not listed as a regulated drug in many countries. ● GC–MS, LC–HRMS NMR, and single-crystal X‐ray diffraction data were presented. Graphical Abstract: A suspicious powder was seized from smugglers who had been monitored for three years by law enforcement officers. Through the use of GC–MS, LC–HRMS NMR, and single-crystal X‐ray diffraction analysis, the powder was identified as 2-(2-chlorophenyl)- 2-nitrocyclohexanone, which can be used as a precursor for the synthesis of norketamine. ga1 Abstract: The identification of new psychoactive substances (NPSs) and their precursors is crucial to understand trends in NPSs so that they can be regulated before they pose a serious threat to human health. In this case, 24 bags containing approximately 600 kg of yellow powder were seized; the smugglers had been monitored for 3 years by the officers of Taiwan's Ministry of Justice Investigation Bureau. A handheld Raman analyzer yielded a positive result for N -boc norketamine; thus, the seized powder was sent to this laboratory for confirmation through gas chromatography-mass spectrometry, liquid chromatographyhigh-resolution mass spectrometry, proton nuclear magnetic resonance ( 1 H NMR), carbon-13 nuclear magnetic resonance ( 13 C NMR), two-dimensional correlation NMR measurements (2D_COSY), heteronuclear single-quantum correlation NMR measurements (2D_HSQC), and single-crystal X‐ray diffraction. This thermolabile powder was subsequently identified as 2-(2-chlorophenyl)- 2-nitrocyclohexanone (2-CPNCH), which can be employed as a precursor for the synthesis of norketamine and is available commercially. Norketamine has similar pharmacological effects to ketamine and phencyclidine but is not regulated in many countries. In this case report, mass fragments, 1 H NMR, 13 C NMR, 2D_COSY, and 2D_HSQC data of 2-CPNCH are presented; moreover, how criminals exploit the loopholes in the law for conducting unauthorized drug manufacturing is discussed.